Posture Detection on Active and Inactive Vertebrae of Spine Biomechanics in Critical Daily Activities / Wan Aliff Abdul Saad...[et al.] - Abdul Saad, Wan Aliff; Mat Dzahir, Mohd Azuwan; Mohamed, Hussein; Ahmad, Zair Asrar; Mohamad, Maziah; Mad Saad, Shaharil; Mat Dzahir, Mohd Azwarie (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The biomechanical principles of orthotic design assist in promoting control, correction, stabilization, or dynamic movement. All orthotic designs are based on three relatively simple principles pressure, equilibrium, and the lever arm principle. The following principles provide the foundation for all orthotic designs keeping in mind that the more complicated the orthotic application, the more confounded the various principles become. The drawbacks of the spinal orthosis cause discomfort, osteopenia (Low BMD), skin breakdown, nerve compression, poor patient compliance etc,. Without a good design implementation and strategy, the deficiency from using this spinal orthosis to the spinal patients might not be solved. Therefore, the previously developed spinal orthosis should be reviewed thoroughly in order to analyse the problem relating to the orthosis development. In addition, we were also able to classify an on-going research in this rehabilitation spinal orthosis field. According to the literature review analysis, it shows that none have tried to control the spinal motion of the vertebrae of the cervical, thoracic, and lumbar curves extensively using a multiple joint spinal orthosis, which will be the main focuses in this article review analysis